Prevention before intervention: introducing mindfulness-based social-emotional learning in higher education institutions across the United Arab Emirates - Kassie, Seada A. (Frontiers in Education, 2023)
In recent years, several studies have indicated that there is a considerable mismatch between the specific set of skills that employers require and the ones that university graduates have to offer. The 2023 report from the World Economic Forum lists 10 core skills that are sought after by global organizations, six of which are categorized under social-emotional learning. As part of its National Employment Strategy 2031, the United Arab Emirates (UAE) aims to build a knowledge-based economy and increase labor productivity. This communicative piece proposes a policy reform across higher education institutions in the United Arab Emirates, seizing as an opportunity the country’s growing commitment to increase talent attraction and retention in the rapidly evolving workplace. Seeing the significant association between social-emotional competencies and thriving in dynamic professional settings, the article highlights the prevalence of mental health disorders among the general youth in the UAE, the government’s commitment towards awareness and prevention of mental health disorders, the relevance of social-emotional competencies for employability and adaptability in the rapidly evolving workplace, the importance of introducing lessons and training in mindfulness-based social-emotional learning (MBSEL) to build the youth’s adaptability in an ever-changing job landscape, and practical measures that can be taken at the institutional level within the UAE context.